WHY DO NATIONS WAR: IDEOLOGY, TERRITORY, POWER AND SECURITY? - Dr Zia Ul Haque Shamsi (International Journal of Contemporary Issues in Social Sciences, 2023)
Warfare remains the most ancient form to resolve disputes, whereas everything has been transformed. Bilateral Treaties, Agreements, Multilateral Treaties, the League of Nations, and the United Nations have not been able to avoid or prevent wars between states, particularly with territorial disputes. However, the most painful military engagements are those that happen between Unequal Military Powers (UMPs), even if they are not for territorial disputes, particularly in modern times. The realists’ worldview manifests wars and conflicts in all their forms in pursuance of power and security by respective states, primarily in their best ‘national interests.’ Historically, the most common reasons for wars between states have been for territory, independence, resources, and support for allies etc. However, this author has acronymized WAR as ‘Waste of Available Resources’ and therefore, this article is aimed at highlighting the deaths and destructions caused by wars, without any considerable gains for the warring states. The objective is to avert the next war between the UMPs to save the relatively weaker states from destruction. Deploying deductive reasoning and retrospective data, an effort is made to create awareness, understanding, and realization among the stakeholders to invest efforts and energies for the public good, instead of wasting the available resources in causing deaths and destruction of the weak.